2001
DOI: 10.1177/0145482x0109500802
|View full text |Cite
|
Sign up to set email alerts
|

Health Conditions, Activity Limitations, and Participation Restrictions among Older People with Visual Impairments

Abstract: Data from the Second Supplement on Aging (1994) were analyzed to evaluate the presence of selected medical conditions, performance of basic and instrumental activities of daily living, and participation in life situations in two groups of visually impaired elders (persons aged 70–74 and persons aged 85 years or older) and two other groups of elders in the same age groups who are not visually impaired. Results indicated that, for both age groups, visual impairment is a significant risk factor for additional med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 18 publications
4
60
0
4
Order By: Relevance
“…They were also found to rate their QoL lower when asked to do so on a 1-5 scale. This pattern of responding has been reported in a number of earlier studies [1][2][3][4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…They were also found to rate their QoL lower when asked to do so on a 1-5 scale. This pattern of responding has been reported in a number of earlier studies [1][2][3][4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 78%
“…Studies of older persons living in the community consistently indicate that those who have difficulty seeing have a high rate of functional disability (i.e., performing activities of daily living including mobility) [1,2], are less well-off economically [3,4], more often socially isolated or lonely [5,6], have more concomitant health conditions [3,7], exhibit poorer physical and mental health [7], and express less satisfaction with life [8] than those who do not. As such, it is generally claimed that visual disability has an adverse affect on quality of life (QoL) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Crews and Campbell (2001) has previously reported that elderly people aged 70 and older with visual impairment often encounter activity limitations. This makes them less physically active and leads to reduced physical functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Sleeuwenkoek et al [9] reported that children with visual impairments walk stiffly and hesitantly and demonstrate balance difficulties, while Pogrund and Rosen [10] indicated that congenitally blind preschool children demonstrate posture anomalies, especially a backward lean of the trunk. In older adults with visual impairments, the loss of balance and mobility present barriers for independence that are also associated with a fear of falling [4,[11][12][13]. Although balance seems to be affected in individuals with visual impairments, this occurrence does not explain the specific www.elsevier.com/locate/gaitpost Available online at www.sciencedirect.com components of balance that are affected.…”
Section: Introductionmentioning
confidence: 99%